Investigation of Slim Type BLDC Motor Drive with Torque Ripple Minimization using Abridged Space-Vector PWM Control Method - C. Bharatiraja; Shyam Babu; V. Krishnakumar; P. Sanjeevikumar; Nixon George (Institute of Advanced Engineering and Science, 2017)
Brushless DC (BLDC) motors are becoming an increasingly popular motor of choice for its unique characteristics. The BLDC motor drive is assumed to have trapezoidal back-electromotive force (EMF), rectangular phase currents and together produces the desired torque. However, practical back-EMF waveform might not be exactly trapezoidal because of current ripple, design considerations and manufacturing limitations. The adverse effect is the torque ripple generated due to the current ripple that causes mechanical vibration, acoustic noise and affects the accuracy of speed and position control which is not desirable in motor operation. In this paper an algorithm is developed to control and minimize the generated torque ripple using Space Vector Pulse Width Modulation (SVPWM) scheme. The efficiency improvement of slim type BLDC motor is confirmed using MATLAB environment and low cost TI Piccolo F28035 microcontroller (MC).